Personalized, interdisciplinary approach to the treatment of chronic low back pain: clinical observation - V. A. Golovacheva; A. A. Golovacheva (Медицинский совет, 2020)
Nonspecific (musculoskeletal) pain is the most common cause of low back pain (LBP). Chronic nonspecific LBP is a particular problem, as it significantly reduces the quality of life and functional activity of the patient. The diagnosis of chronic non-specific LBP is made after exclusion of a specific cause of pain, discogenic radiculopathy and lumbar stenosis. Unfortunately, patients with chronic non-specific LBP are often misdiagnosed, pain chronization factors (“yellow flags”) are ignored and ineffective treatment is prescribed. Clinical observation of a patient with chronic non-specific LBP, who was initially wrongly diagnosed with spinal osteochondrosis and the treatment was ineffective, is presented. A personalized, multidisciplinary approach to treatment allowed the patient to cope with back pain and to return to his previous daily activities. The patient’s treatment plan included non-drug methods of treatment (educational conversation, physical activity, mindfulness, cognitive-behavioural therapy) and rational pharmacotherapy (non-steroidal anti-inflammatory drug, NSAID). Clinical observation showed the efficacy and good tolerability of NSAID - dexketoprofen (in the form of Dexalgin and Dexalgin 25), which was administered in a stepwise scheme for 5 days. According to modern recommendations, NSAIDs are first-line drugs in chronic non-specific LBP. The results of clinical studies on efficacy and safety in back pain of such NSAIDs as dexketoprofen and nimesulide are presented. In case of prolonged exacerbation the possibility of dexketoprofen prescription with subsequent transition to nimesulide is discussed.